RELATIONSHIP BETWEEN PROFESSIONAL ADVICE AND USE OF NEW TECHNOLOGIES IN HORTICULTURAL FARMS OF LA PLATA, ARGENTINA - CIEZA, Ramón Isidro (Scientia Agraria, 2004)
Between 1990 - 2001, in the horticultural sector of La Plata, Argentina, important changes was taken place because the adoption of greenhouse cultivation and a group of complementary technologies. The incorporation degree of these new technologies and their productive - commercial success was variable according to the farmers type and their possibilities of adaptation to these changes. The hypothesis is that those farmers that adopted successfully new technological packages, developing a best managerial profile, have had professional advice. The aim of this work is to study the technological-commercial heterogeneity of the horticultural farms and the incidence of the technical advice in this heterogeneity. 30 surveys to horticultural farmers were carried out between February and May of 2004 in three representative sections of the Horticultural Area of La Plata, Argentina. 10 variables were determined (4 about each producer and 6 in relationship with their production - commercialization ways). This variables were analyzed using multivariate and bivariate statistical methods. Three groups of horticultural farms were identified according to the type of technologies used, the way to access to technical knowledge and the utilized commercialization channels. Relationships between farmers characteristics and the technical-commercial management of each farm was not found. We concluded that technical advisers have favorably influenced in the adaptation of the new technological models, preponderantly in managerial farmers.